The city of Mexico in the age of Díaz - Johns, Michael, 1958- (University of Texas Press, 1997)
"Strange anti-Porfirista depiction of social conditions in the city without reference to major actors such as Weetman Pierson or to other major cities during the same era. Offers only the 'official history,' demonstrating Díaz's lack of concern for everyone except his cronies"--Handbook of Latin American Studies, v. 58.